"I don't want financial support but verbal support." How do caregivers manage children's access to and retention in HIV care in urban Zimbabwe?. Issue 2 (9th May 2014) - Busza, Joanna; Dauya, Ethel; Bandason, Tsitsi; Mujuru, Hilda; Ferrand, Rashida A
Abstract : Introduction: Children living with HIV experience particular challenges in accessing HIV care. Children usually rely on adult caregivers for access to care, including timely diagnosis, initiation of treatment and sustained engagement with HIV services. The aim of this study was to inform the design of a community‐based intervention to support caregivers of HIV‐positive children to increase children's retention in care as part of a programme introducing decentralized HIV care in primary health facilities. Methods: Using an existing conceptual framework, we conducted formative research to identify key local contextual factors affecting children's linkages to HIV care in Harare, Zimbabwe. We conducted semi‐structured interviews with 15 primary caregivers of HIV‐positive children aged 6–15 years enrolled at a hospital clinic for at least six months, followed by interviews with nine key informants from five community‐based organizations providing adherence support or related services. Results: We identified a range of facilitators and barriers that caregivers experience. Distance to the hospital, cost of transportation, fear of disclosing HIV status to the child or others, unstable family structure and institutional factors such as drug stock‐outs, healthcare worker absenteeism and unsympathetic school environments proved the most salient limiting factors. Facilitators included openness within the family, availability of practical assistance and psychosocial support from community members. Conclusions: The proposed decentralization of HIV care will mitigate concerns about distance and transport costs but is likely to be insufficient to ensure children's sustained retention. Following this study, we developed a package of structured home visits by voluntary lay workers to proactively address other determinants such as disclosure within families, access to available services and support through caregivers' social networks. A randomized controlled trial is underway to assess impact on children's retention in care over two years.